Effect of Antibiotics on Polymorphonuclear Leukocyte Functions and Myeloperoxidase Activity, Glutathione and Malondialdehyde Levels in Allergic Asthma - (:unkn) unknown (POLSKIE TOWARZYSTWO MIKROBIOLOGOW-POLISH SOCIETY OF MICROBIOLOGISTS, 2015)
We investigated the effect of ciprofloxacin, rifampicine and doxycydine on myeloperoxidase (MPO) activity, glutathione (GSH) and malondialdehyde (MDA) levels in allergic asthma patients and healthy volunteers. Polymorphonudear leukocytes(PMNs) were isolated with ficoll-hypaque gradient centrifugation method. MPO activity was assayed with modified o-dianisidine, GSH by Ellman's and MDA levels by Beuge's method. PMN functions and MDA levels of patients significantly decreased when compared with healthy volunteers. Ciprofloxacin significantly increased PMN functions, MPO activity and MDA levels of both groups. We have demonstrated that ciprofloxacin has beneficial effects on MPO activity and PMN functions in allergic asthma patients and healthy volunteers.
Keywords: allergic asthma; antibiotics; intracellular killing activity; myeloperoxidase; phagocytosis; IMMUNOTHERAPY; RHINITIS